2004
DOI: 10.1093/ps/83.6.868
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Economic Optimum Level of Calcium in White Leghorn Laying Hens

Abstract: Calcium is important in eggshell formation; inadequate levels in the diet of laying hens may affect shell quality and egg production. An experiment with 250 Leghorn Hy-Line W-98 hens was conducted to evaluate 5 dietary Ca levels (2.96, 3.22, 3.83, 4.31, and 4.82%) in 3 laying periods. The evaluated variables were egg production (EP), egg mass (EM), average daily feed intake (ADFI), feed conversion (FC), and specific gravity (SG). The biological optimum level (BOL) of Ca for maximum egg production and specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 12 publications
2
16
0
1
Order By: Relevance
“…Similar results were obtained in a study conducted on Hy-Line layers, where increasing the dietary Ca level from 3.1 to 3.7% resulted in a significant linear improvement of eggshell quality (Sohail and Roland, 2000). The significant effect of the dietary Ca level on the eggshell was also observed by Castillo et al (2004), who noticed that shell specific gravity was greater in hens fed a diet with 3.83% Ca than in those receiving 2.96% Ca; however there were no significant differences between the Ca levels of 3.22 and 3.83%. Safaa et al (2008) reported that eggshell percent, thickness and density significantly increased when the dietary level of Ca was raised from 3.5 to 4.0%.…”
Section: Eggshell Qualitysupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were obtained in a study conducted on Hy-Line layers, where increasing the dietary Ca level from 3.1 to 3.7% resulted in a significant linear improvement of eggshell quality (Sohail and Roland, 2000). The significant effect of the dietary Ca level on the eggshell was also observed by Castillo et al (2004), who noticed that shell specific gravity was greater in hens fed a diet with 3.83% Ca than in those receiving 2.96% Ca; however there were no significant differences between the Ca levels of 3.22 and 3.83%. Safaa et al (2008) reported that eggshell percent, thickness and density significantly increased when the dietary level of Ca was raised from 3.5 to 4.0%.…”
Section: Eggshell Qualitysupporting
confidence: 86%
“…A similar tendency toward the negative effect of the hen's age on eggshell quality was reported by Al-Batshan et al (1994), De Ketelaere et al (2002 and Swiatkiewicz and Koreleski (2008), among others. In White Leghorn hens in the late laying phase (55 to 70 weeks of age), eggshell quality, measured as shell specific gravity, was significantly lower than in younger birds (Castillo et al, 2004). In this study, reducing the dietary levels of Ca and P negatively affected eggshell quality parameters throughout the whole experimental period (at 34, 46, 58 and 70 weeks of age).…”
Section: Eggshell Qualitymentioning
confidence: 45%
“…However, Castillo et al (2004) reported that these traits were not affected when Ca intake increased from 3.68 to 4.26 g/d (3.22 to 3.83% of the diet) in SCWL hens from 55 to 70 wk of age. In addition, Roland and Bryant (1994) indicated that as Ca intake increased from 3.58 to 4.35 g/d (3.3 to 4.1% of the diet), ADFI decreased, but neither egg production nor egg weight was affected in SCWL from 24 to 27 wk of age.…”
Section: Productive Performance and Egg Qualitymentioning
confidence: 96%
“…In the presence of 150, 300, and 400 phytase units (FTU)/kg of feed, the dietary NPP level may be decreased, and optimal levels were calculated as being 1.8, 1.5, and 1.4 g/kg, respectively. In addition, Al-Massad et al (2011) found that 1.2 g/kg NPP appears to be sufficient for maintaining production performance and eggshell quality in hens fed a corn-soybean meal diet containing 34 g/kg Ca and supplemented with F. On the other hand, Castillo et al (2004) showed that the biological optimum levels of Ca for maximum egg production and specific gravity were 43.4 and 46.0 g/kg, respectively, and the economic optimum level for maximizing profits was 43.8 g/kg in diets containing 4.0 g/kg AP.…”
mentioning
confidence: 99%